Employee Engagement in Philosophical Review: Ontology, Epistemology, and Axiology - Sudrajat, Jajat; Siow, Hong Loke; Permana, Ibar Adi (Indo Consultan Energi, 2025)
This study aims to describe employee engagement from a philosophical perspective, through three main dimensions: ontology, epistemology, and axiology. The method used is a literature study that examines various relevant scientific references. This study examines the nature of engagement ontologically, the basis and source of its epistemological knowledge, and the value and appropriateness of its implementation axiologically. The study's results show that ontologically, employee engagement is a reality reflected in work behavior full of enthusiasm, dedication, and absorption. Epistemologically, engagement is understood as a scientific construct developed through valid theories, data, and research methods. On the other hand, engagement has strategic value axiologically because it contributes to forming work ethics, loyalty, and organizational productivity. The implication is that paying attention to employee engagement within a philosophical framework is important to provide a strong conceptual foundation in formulating competent and sustainable human resource development strategies.